ZINC SEED PRIMING IMPROVES STAND ESTABLISHMENT, TISSUE ZINC CONCENTRATION AND EARLY SEEDLING GROWTH OF CHICKPEA - A. Ullah; M. Farooq; M. Hussain; R. Ahmad; A. Wakeel (Journal of Animal and Plant Sciences, 2019)
Zinc (Zn) deficiency is one of the major factors causing substantial loss to chickpea production. Zinc can be applied by several means including seed priming. Before field application, optimization of Zn seed primingis requiredas both toxicity and deficiency of Zn badly impacts chickpea growth and productivity. Therefore, this study was conducted to optimize the Zn concentration forseed priming in both desi and kabuli chickpea. For this, four independent experiments were performed both in petri plates and sand filled small pots. In petri plates, seeds were sown between the layers of moist filter papers, while in sand filled pots, seeds were sown in small sand filled (500 g) pots. In the first two experiments, Zn was applied using different seed priming concentrations viz.,0.01, 0.05, 0.1, 0.5, 1.0 M Zn and no Zn was taken as control. At all these Zn seed priming concentrations,there was no germination/emergence owing to Zn toxicity (data not given).In third and fourth experiments, based on above results, the Zn concentrationswere reduced to0.01, 0.001and 0.0001 MZn solutions,taking non-primed seeds as control. The mean germination/emergence time and seedling growth of both chickpea typeswereimproved with Zn seed priming in 0.001 and 0.0001 M Zn solution except 0.01 M Zn that caused toxicity.In both experiments, seed priming with 0.001 M Zn decreased mean germination/emergencetime, improvedthe seedling root(47.8 and 30.4%)and shoot length (27.1 and 10.9%),number of secondary roots(80.0 and 28.6%),seedling dry weight (25.5 and 42.5%) and seedling Zn concentration(30.3 and 47.2%),respectively in petri plates and sand filled pots in both chickpea types. In conclusion, seed priming ≥ 0.01 M Zn proved toxic. Chickpea seed may be primed with 0.001 MZn to improvethe seedling germination/emergence and early seedling growth.
Keywords: Deficiency; toxicity; germination rate; root length; seedling dry weight